2010
DOI: 10.1039/c0mt00010h
|View full text |Cite
|
Sign up to set email alerts
|

A study of the distribution of aluminium in human placental tissues based on alkaline solubilization with determination by electrothermal atomic absorption spectrometry

Abstract: SummaryAluminum (Al) is a nonessential element known to induce neurotoxic effects, such as dialysis dementia, in patients on hemodialysis, with compromised kidney function. The role of Al in the progression of some neurodegenerative diseases, such as Alzheimer's disease (AD), is controversial, and remains unclear. The effects of Al on other vulnerable populations, such as fetuses and infants, have been infrequently studied. In the present study, Al has been measured in human placenta samples, comprising ~160 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…The linear regression best fit slope of the placental Al concentrations is greater than the slope of the fetal Al concentrations, further indicating greater Al distribution into the placenta than fetus. Similarly, a study that quantified Al in the placental body and membrane and umbilical cord found less Al in the cord (0.56 and 0.53 versus 0.27, respectively) (Kruger et al 2010). A normally distributed transform of the testes Al concentration as a multiple of the Al concentration in animals that did not receive additional Al (Table 10) was not identified.…”
Section: (2262)mentioning
confidence: 93%
“…The linear regression best fit slope of the placental Al concentrations is greater than the slope of the fetal Al concentrations, further indicating greater Al distribution into the placenta than fetus. Similarly, a study that quantified Al in the placental body and membrane and umbilical cord found less Al in the cord (0.56 and 0.53 versus 0.27, respectively) (Kruger et al 2010). A normally distributed transform of the testes Al concentration as a multiple of the Al concentration in animals that did not receive additional Al (Table 10) was not identified.…”
Section: (2262)mentioning
confidence: 93%
“…High concentration of Al in human semen as well as the presence of Al in spermatozoa have been reported in patients with deteriorated semen quality, which suggests possible implications of Al in spermatogenesis and sperm count [ 16 ]. An analytical study on placenta tissues showed that Al was present in 95% of placenta body samples and 81% of placenta membrane samples, but only in 46% of umbilical cord samples, which indicates that the placenta acts as a partial barrier to Al exposure in utero [ 17 ]. The authors concluded that the developing fetus may still be vulnerable to cumulative Al exposure and that it is, therefore, important to establish reference ranges for Al levels in placental tissues [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…An analytical study on placenta tissues showed that Al was present in 95% of placenta body samples and 81% of placenta membrane samples, but only in 46% of umbilical cord samples, which indicates that the placenta acts as a partial barrier to Al exposure in utero [ 17 ]. The authors concluded that the developing fetus may still be vulnerable to cumulative Al exposure and that it is, therefore, important to establish reference ranges for Al levels in placental tissues [ 17 ]. Exposure to toxic metals including Al has been recently investigated as a potential cause of miscarriages [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SPH students have been first authors on numerous DOH/SPH studies published jointly, including an MCH-funded study related to the control of rabies risk in children, 19 and a collaborative environmental health article selected as the journal's cover page. 20 In addition to the benefits to research and program evaluation, the opportunity to teach and be involved in an academic environment increases the DOH's ability to recruit, retain, and improve the skill level of its professional and scientific staff. A skilled professional workforce improves the DOH's ability to assess health problems and to design and evaluate public health programs in the state.…”
Section: • Benefits Of the Ahd Model To The Doh And Public Health In mentioning
confidence: 99%